2021
DOI: 10.1093/plcell/koab280
|View full text |Cite
|
Sign up to set email alerts
|

The miRNome function transitions from regulating developmental genes to transposable elements during pollen maturation

Abstract: Animal and plant microRNAs (miRNAs) are essential for the spatio-temporal regulation of development. Together with this role, plant miRNAs have been proposed to target transposable elements (TEs) and stimulate the production of epigenetically active small interfering RNAs. This activity is evident in the plant male gamete containing structure, the male gametophyte or pollen grain. How the dual role of plant miRNAs, regulating both genes and TEs, is integrated during pollen development and which mRNAs are regul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 93 publications
2
11
0
Order By: Relevance
“…We also looked at the expression patterns of the small RNA machinery, given its prominent role in pollen biology. 45 , 46 As previously described, 45 , 46 we found that AGO5 was expressed in GN and AGO1 in microspores and VN ( Figure S5K ).…”
Section: Resultssupporting
confidence: 82%
“…We also looked at the expression patterns of the small RNA machinery, given its prominent role in pollen biology. 45 , 46 As previously described, 45 , 46 we found that AGO5 was expressed in GN and AGO1 in microspores and VN ( Figure S5K ).…”
Section: Resultssupporting
confidence: 82%
“…We also looked at the expression patterns of the small RNA machinery, given its prominent role in pollen biology (Borges et al, 2011;Oliver et al, 2022). As previously described, we found that AGO5 was expressed in the GN and AGO1 in microspores and VN (Figure S5K).…”
Section: Single Nucleus Rna-seq Reveals the Transcriptional Landscape...supporting
confidence: 55%
“…Of note, the H3K27 methyltransferases CURLY LEAF ( CLF ) and SWINGER ( SWN ) were enriched in the VN and depleted from SN, which is consistent with a recent report of the erasure of H3K27 in sperm nuclei (Borg et al, 2020). We also looked at the expression patterns of the small RNA machinery, given its prominent role in pollen biology (Borges et al, 2011; Oliver et al, 2022). As previously described, we found that AGO5 was expressed in the GN and AGO1 in microspores and VN (Figure S5K).…”
Section: Resultsmentioning
confidence: 99%
“…AGOs can form RNA-induced silencing complexes (RISC) by binding 21–22 nt siRNAs and then mediating RNA cleavage leading to translational inhibition or participating in the RdDM pathway by binding 24 nt siRNAs [ 95 ]. In Arabidopsis , AtAGO1 is located in the pollen VC nucleus [ 96 ], and AtAGO5 accumulates in the SC cytoplasm [ 97 ], which makes the major AGO protein substances active in the mature pollen [ 86 ]. Weak mutants of ago1 and dcl1 showed pollen developmental defects and led to aborted or shrunken mature pollen grains, while strong ago1 and dcl1 mutants failed to develop gametes [ 98 , 99 ], indicating their essential role in gametophyte development.…”
Section: Epigenetic Regulation-related Genes That Are Involved In Pol...mentioning
confidence: 99%